Control of primary lesions using resection or radiotherapy can improve the prognosis of metastatic colorectal cancer patients. Issue 1 (25th April 2016) - Takada, Takahiro; Tsutsumi, Soichi; Takahashi, Ryo; Ohsone, Katsuya; Tatsuki, Hironori; Suto, Toshinaga; Kato, Toshihide; Fujii, Takaaki; Yokobori, Takehiko; Kuwano, Hiroyuki
Abstract : Background: Control of the primary lesions in metastatic colorectal cancer (mCRC) is still controversial. For rectal cancer patients, not only resection but also irradiation is expected to provide palliative effects. We investigated the effects of resection and irradiation of primary lesions (local control) on the prognosis of mCRC patients. Patients: Forty‐seven patients with mCRC at our institute were examined, with 34 in the local controlled group and 13 in the uncontrolled group. Results: The median survival time (MST) of the local controlled and uncontrolled groups were 2.90 and 1.39 years ( P  = 0.028). Cox proportional hazard regression analysis showed that local control was an independent prognostic factor ( P  < 0.05). The patients who underwent primary lesion resection had significantly longer MST (2.90 vs. 1.39 years, P  = 0.032) than those in the uncontrolled group. In rectal cancer patients, the patients who underwent irradiation to control the primary lesions had a significantly longer MST than the uncontrolled patient group (1.97 vs. 1.39 years, P  = 0.019). Conclusions: Local control of primary lesions may improve the prognosis in mCRC patients. In rectal cancer patients with metastasis, not only resection but also irradiation of the primary lesions may be a useful therapeutic strategy. J. Surg. Oncol. 2016;114:75–79 . © 2016 Wiley Periodicals, Inc.